2001
DOI: 10.1073/pnas.101124798
|View full text |Cite
|
Sign up to set email alerts
|

Crystal cataracts: Human genetic cataract caused by protein crystallization

Abstract: Several human genetic cataracts have been linked recently to point mutations in the ␥D crystallin gene. Here we provide a molecular basis for lens opacity in two genetic cataracts and suggest that the opacity occurs because of the spontaneous crystallization of the mutant proteins. Such crystallization of endogenous proteins leading to pathology is an unusual event. Measurements of the solubility curves of crystals of the Arg-58 to His and Arg-36 to Ser mutants of ␥D crystallin show that the mutations dramatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
207
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 206 publications
(225 citation statements)
references
References 23 publications
10
207
0
2
Order By: Relevance
“…70 In addition, point mutations associated with congenital cataracts also involve surface polar residues of c-crystallins. 71,72 Taken together, aforementioned experimental observations suggested that the surface charge network, together with the hydrophobic interactions, plays a major role in maintaining the stability of native cD-crys. The greater abundance of acidic and basic residues within the C-td most likely adds to its higher stability over the N-td in the native state.…”
Section: Resultsmentioning
confidence: 88%
“…70 In addition, point mutations associated with congenital cataracts also involve surface polar residues of c-crystallins. 71,72 Taken together, aforementioned experimental observations suggested that the surface charge network, together with the hydrophobic interactions, plays a major role in maintaining the stability of native cD-crys. The greater abundance of acidic and basic residues within the C-td most likely adds to its higher stability over the N-td in the native state.…”
Section: Resultsmentioning
confidence: 88%
“…Over the last decade, we have focused on the point mutations occurring in human γD-crystallin (HGD), a member of the γ-crystallin family expressed at high levels along with γC-and γS-crystallins in the human lens (5). By comparing the properties of several mutants of HGD in solution with those of the wild type, we have identified specific changes in the homologous (i.e., γ-γ interactions) that led to the formation of distinct condensed phases (6,7) and accounted for the increased light scattering due to these mutations (8)(9)(10)(11)(12)(13). These studies revealed a class of γ-crystallin mutations in which small changes to the protein surface were sufficient to bring about severe solubility changes, without unfolding the protein, and were in direct contrast to other mutations (i.e., other missense mutations, insertions, and splice mutations) that are accompanied by alterations in protein fold and stability (1,14,15).…”
mentioning
confidence: 99%
“…Mutation at site 23 of HGD is only one of a number of single point mutations, including the R14C, R58H, and R36S mutations, that occur on the CRGD gene and that have been linked with early-onset cataract disease (5)(6)(7)(8)(9). Physicochemical characterization of the mutant proteins shows why these changes result in the formation of either covalently linked aggregates in the case of R14C (5,6) or crystals in the case of the R58H and R36S mutants (7)(8)(9). The P23T mutation results in decreased solubility of the protein, leading to protein aggregation and light scattering, and hence to lens opacity.…”
mentioning
confidence: 99%